Interactions of Neisseria gonorrhoeae with human neutrophils: studies with purified PII (Opa) outer membrane proteins and synthetic Opa peptides. - Naids, F L (1991)
We investigated the role of gonococcal outer membrane protein PII (also called Opa protein) in nonopsonic adherence to human neutrophils. Gonococcal outer membranes, purified Opa in detergent (Opa), purified Opa in liposomes (Opa+ lips), and peptides composing the second hypervariable (HV2) region of OpaB (strain FA1090) in liposomes (pepHV2 lips) were tested for their abilities to inhibit subsequent gonococcal adherence to human neutrophils. Outer membranes from gonococci possessing adherent Opa, liposomes containing adherent Opa, purified adherent Opa, and two of three liposome preparations (pepHV2 lips) containing peptides from the HV2 region of an adherent Opa inhibited subsequent adherence to neutrophils of homologous Opa+ gonococci. On the other hand, outer membranes from Opa- gonococci, outer membranes containing a nonadherent Opa (OpaA from strain FA1090), purified OpaA, and OpaA lips had little or no inhibitory effect. Outer membranes containing adherent Opas, purified adherent Opas, and liposomes containing such Opas all bound to neutrophils, whereas preparations containing OpaA or no Opa protein did not. The results indicate that (i) Opa proteins can bind to neutrophils in a partially purified or purified form and (ii) the HV2 region of Opa appears to at least partially mediate Opa's biological role.